How the Irish became “Gauchos Ingleses”: Diasporic Models in Irish-Argentine Literature - Murray, Edmundo (ABEI Journal, 2004)
Declan Kiberd argues that “postcolonial writing does not begin only when the occupier withdraws: rather it is initiated at that very moment when a native writer formulates a text committed to cultural resistance.” Paradoxically, the Irish who emigrated to Argentina, a former Spanish colony, may be regarded (as they may have regarded themselves) as colonised in the country they left, and as colonisers of their new home. Their case is one of the better counterexamples to the typical pattern of identities in most of the English-speaking destinations of the Irish Diaspora. Using William Bulfin’s Tales of the Pampas as primary document, in this article I search the identities represented in his characters. In Tales of the Pampas, Bulfin amalgamates the ambiguous acculturation of the Irish settlers with that of the “gaucho” (those cowboys of the South American pampas who almost literally lived in the saddle), as well as with the symbols of Gauchesca narrative. Evolving from colonised to colonisers during their initial settlement, the Irish in Argentina swiftly became ingleses. In the following decades, in order to join the local bourgeoisie they were required to be gauchos, and to show signs of their effective integration to the native culture, as seen by the Argentine elites. This explains why most of the successful Irish settlers gradually separated from the Anglo-Argentine mainstream culture and shaped their own community. A negotiation of identities among Irishness, Britishness, and Argentineness was always in place. I argue that these identities are not only unmoored in the emigrants’ minds but also manoeuvred by community leaders, politicians and priests. After reviewing the major milestones of the nineteenth-century Irish emigration to Argentina, the article analyses selected passages from the text, offers a version of how the settlers became Irish-Argentines, and elucidates some of the processes which created the new Irish-Argentine hybrid.